Central and Peripheral Adiposity Had Different Effect on Disability in Centenarians - Yang, Shanshan; Wang, Shengshu; Tai, Penggang; Jia, Wangping; Han, Ke; Liu, Miao; He, Yao (Frontiers in Endocrinology, 2021)
Purpose: To explore the correlations between waist circumference, body mass index, calf circumference (CC), and waist-calf circumference ratio (WCR) and activities of daily living (ADLs) and instrumental activities of daily living (IADLs) in Hainan centenarians. Patients and methods: A total of 1002 Hainan centenarians were selected by full sample household survey. ADLs and IADLs were used to investigate the ability of activity and instrumental activity in daily living. The possible non-linear associations were further analyzed using restricted cubic spline. Results: After adjusting for demographic characteristics (gender, age, ethnicity, marital status, educational level, and type of residence) and lifestyle (smoking, drinking, and exercise), the odds ratio (OR) of CC (continuous variable) on ADL disability in centenarians was 0.90 (95% CI: 0.85–0.96), while high WCR (continuous variable) was related with high risk of ADL disability (OR=1.73; 95% confidence interval[CI], 1.07–2.80). The ORs of CC and WCR for IADL severe disability were 0.86 (95% CI, 0.82–0.91) and 2.23 (95% CI, 1.52–3.28), respectively. Conclusion: Central (WCR) and peripheral (CC) adiposity had different effects on disability (ADL and IADL) in centenarians. Even in centenarians, maintaining muscle mass (with higher calf circumference) and avoiding central obesity are of positive significance for the prevention of ADL/IADL disability.